DEVELOPMENT OF A NEW DETECTOR SYSTEM TO EVALUATE POSITION AND ACTIVITY OF PLUTONIUM PARTICLES IN NASAL CAVITIES. Issue 4 (8th September 2017) - Morishita, Yuki; Yamamoto, Seiichi; Momose, Takumaro; Kaneko, Junichi H; Nemoto, Norio
Abstract: Plutonium dioxide (PuO2 ) is used to fabricate a mixed oxide fuel for fast breeder reactors. When a glove box containing PuO2 fails, such as by rupture of a glove or a vinyl bag, airborne contamination of plutonium (Pu) can occur. If a worker inhales PuO2 particles, they will be continually irradiating their lung tissue with alpha particles, and this could cause lung cancer. The nasal smear and nose blow methods are useful for checking workers for PuO2 intake in the field. However, neither method can evaluate the quantitative activity of Pu. No alpha-particle detector that can be used for direct measurements in the nasal cavity has been developed. For direct and quantitative measurement, it is required that a shape of the detector should be a fine bar which inserts itself in the nose to measure the accurate activity of Pu. Therefore, we developed a nasal monitor capable of directly measuring the activity of Pu in the nasal cavity to estimate the internal exposure dose of a worker. Prismatic-shaped 2 × 2 acrylic light guides were used to compose a detector block, and a ZnS(Ag) scintillator was adhered to the surface of these light guides. Silicon photomultiplier (SiPM) arrays with 8 × 8 channels were used as a photodetector. Actual PuO2 particles were measured using the nasal monitor. The nasal monitor could be directly inserted in the nasal cavities, and the activity distribution of Pu was obtained by the nasal monitor. The average efficiencies in 4-pi were 11.4 and 11.6% for the left and right nasal cavities, respectively. The influence of gamma and beta rays from Cesium-137 ( 137 Cs) Strontium-90 ( 90 Sr) on the detection of the alpha particles of Pu was negligible. The difference in the measured Pu activity between the ZnS(Ag) scintillation counter and the nasal monitor was within 4.0%. Therefore, it was considered that the developed nasal monitor could be used in direct Pu determination to estimate the internal exposure dose of workers.